Character Education Based on Minangkabau Local Wisdom - Alhamuddin Alhamuddin; Oki Dermawan; Helmi Azis; Revan Dwi Erlangga (Universitas Negeri Jakarta, 2022)
Character education is the most important thing in the personality of each individual. It is not only influenced by parents and education level, but character education can be influenced by the community environment, including local wisdom in an area. The purpose of this study was to determine the transformation of Islamic education in Minangkabau in relation to Islam and local culture. The research method used was a qualitative approach with ethnographic method, ethnography was used to see how the relationship between Islam and local culture in transforming the concept of Modern Islamic education in Minangkabau. The results showed that Minangkabau local traditional expressions provide guidance and advice so that they always have religious character, honesty, tolerance, responsibility and discipline, fairness, social care, courtesy, friendly and communicative, and high work ethic. Thus it can be stated that all the values ​​of character education that arise from the messages of advice in Minangkabau traditional expressions are in accordance with the Shari'ah and are exemplified by the Prophet Muhammad Saw